Analysis of Individual and Group Behavior in Organizations - Nur Haeni (Konsultan Jurnal Ilmiah Indonesia, 2024)
Humans are social beings. Cannot stand alone without the help of others. Social beings in their lives need other people. This study discusses group behavior in organizations, organizations are groups of people who are working towards common goals under leadership. Every human being in any activity will be involved in group activities. The purpose of this study is to determine various group behaviors in organizations. The method used in this study is the study and analysis of data, especially from journals and books that are related to the topic of writing, data is analyzed using qualitative analysis. The results of this study are There are so many benefits from the existence of groups in an organization, both benefits for individuals as part or members of the group and for the effectiveness of the work of an ongoing organization. Individual behavior must be directed towards the interests of the organization in order to achieve organizational goals so that in further developments group behavior develops into organizational behavior.